The Effectiveness of Acupuncture Therapy and Warm Compresses Combination on Gastritis Pain Scale in Female Students at SMAIT Ibnu Abbas Klaten - Amin, Isna Nur; Nugraha, Nurtama Aditya; Zulaika, Chusnul (Indonesian Journal of Acupuncture, 2024)
Gastritis easily attacks teenagers because of the high academic and is characterized by stomach pain, nausea, and vomiting. Complementary therapies that can be used for gastritis are acupuncture and warm compresses. Acupuncture stimulates the autonomic nerves to inhibit sympathetic stimulation so that vasodilation occurs. Warm compresses can relax muscles, so they can reduce gastritis pain. Research purposes to determine the effectiveness of acupuncture therapy and a combination of warm compresses on the gastritis pain scale in female students at SMAIT Ibnu Abbas Klaten. This research used Quasi Experiment Design with the two groups pretest-posttest design method and Purposive Sampling technique, with a total sample of 34 research subject. The points used are ST 36, PC 6, CV 12, and SP 6, and the warm compress using a water bag at a temperature of 37-40°???? for 15 minutes. Research was conducted at SMAIT Ibnu Abbas Klaten in February–March 2024. The Paired T-test for both groups has p<0.001. Acupuncture therapy and warm compresses are more effective because they have a mean value of 3.294, while the mean value of the acupuncture therapy group is 2.941. Acupuncture therapy and warm compresses combination are effective in reducing the gastritis pain scale.